SYSTEM MODELING OF PROFESSIONAL TRAINING PROCESS FOR FUTURE PRACTICAL PSYCHOLOGISTS IN AVIATION UNIVERSITY - Євтух, М. Б.; Лузік, Е. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article is devoted to the problem of optimizing the process of training future psychologists in higher educational establishments using criteria of system modeling of educational process – didactic invariant elements of educational activities